Economic Production and the Spread of Supernatural Beliefs - Daniel Araújo; Bladimir Carrillo; Breno Sampaio (Institute of Labor Economics (IZA), 2021)
Religion and beliefs in the supernatural are present in all societies. Yet, studies about the spread of small-scale supernatural belief systems remain quite limited. In this work, we test the anthropological hypothesis that historical dependence on pastoralism favored the adoption of customs that contributed to the reduction in witchcraft beliefs. Pastoral societies were characterized by the use of social strategies as a way of mitigating the risks inherent in pastoral production, making the practice of accusations of witchcraft a barrier to maintaining their existing social ties. Consistent with this hypothesis, we document that people descending from historically more pastoral societies have a lower level of contemporary belief in witches. The results using an instrumental variable based on the ecological determinants of pastoralism corroborates our main analysis. We further show that the main mechanism behind our result seems to be pastoralist groups\~Aâ'¬â" freedom of movement and an increase in social ties, proxied by the level of trust in relatives, neighbors, courts, and local councils. We also show that the reduced belief in witches increases references to witchcraft in pastoral societies\~Aâ'¬â" oral traditions, narratives, stories, jokes, and proverbs, possibly because the lack of fear makes pastoralists more willing to speak, sing and joke about the supernatural. Finally, we test for the importance of cultural persistence by examining people who live today in locations with low levels of suitability for pastoralism but belong to ethnic groups that have historically lived in areas with high levels of suitability and show that the reduction in belief in witchcraft persists.
Keywords: O10; Z10; Z13; Z19; 330; culture; pastoralism; persistence; superstition; witchcraft